Research on Intervention Strategies for Cognitive Dysfunction in the Elderly from the Perspective of Social Support Theory - Liu, Liying (International Journal of Global Economics and Management, 2024)
Based on the perspective of social support theory, this paper studies the influence of the social support system on cognitive dysfunction in the elderly, including the impact on the mental health of the elderly, ways to improve the quality of life of elderly patients with cognitive dysfunction, the promoting role in the integration and participation of the elderly in society, the importance of improving the social support system in the intervention and the management of cognitive dysfunction in the elderly. In addition, this paper also proposes the social intervention strategies for cognitive dysfunction in the elderly and evaluates the effect of social support intervention on cognitive dysfunction in the elderly.